Sharp fronts in attracting-adatom monolayers - Wio, H. S. (2014)
The problem of pattern formation by adsorbates undergoing attractive lateral interactions, is described by a parabolic integrodiffer- ential equation having the scaled inverse temperature ε and the scaled pressure α of the vapor phase as parameters. A coexistence region of high- and low-coverage stable homogeneous states has been reported in the (ε, α) plane. In the small interaction-range limit an effectve dif- fusion coefficient can be defined, which becomes however negative for a coverage range in between the stable homogeneous ones. A novel free-energy-like Lyapunov functional is found here for this prob- lem. When evaluated on the homogeneous states, it leads to a Maxwell- like construction which selects essentially the same value α(ε) as the originally posited zero front-velocity condition. Moreover, its value on static fronts at this particular α(ε) coincides with those of the homo- geneous states. This article is dedicated to Prof. Helmut Brand with occasion of his 60th birthday.